Peranan Ikatan Pelajar Muhammadiyah (IPM) dalam Mencegah Penyebaran Paham Radikalisme yang Memicu Terorisme pada Siswa-Siswi SMA Muhammadiyah 4 Jakarta Timur - Marjan Miharja; Riyanta Riyanta; Nur Alam B.; Sonia Yekti H.; Pujantini Pujantini; Eko Agus S.; Dimas Widya Pradana; Riki Andreas S.; Deden Adith Fauzan; Beato Dionisius L.; Paternus Alvian L.; Septya Rizky; Esa Dian Arifni (Joong-Ki : Jurnal Pengabdian Masyarakat, 2023)
Indonesia is now inseparable from the threat of dissolution due to the emergence of radical ideas. The rise of radical movements in Indonesia has caused its own concern among the Indonesian people, because radicalism is closely related to terrorist attacks. The organization of the school plays an important role in creating a successful education. School activities (morning education/learning activities) and extracurricular activities (afternoon education/learning activities) are encouraged by school organizations. An attitude of leading, discipline, and many other positive things can be formed by participating in HDI, so that their talents are more channeled and honed. HDI is a role model for other students, so HDI plays a big role in shaping students' views on how to behave and deal with things, especially radical attitudes that trigger terrorism.